Plankton in a tropical Kanhiraphuza reservoir, Kerala - variation in space and time - Palaniswamy, Rani; Unnithan, Usha; Paul, Thankam Theresa (Journal of the Inland Fisheries Society of India, 2020)
Kanhirapuzha is a perennial reservoir located in the rain fed dense forest of tropical Western Ghats of Kerala state, India where fish production is cultured based.Numerical data on plankton abundances analysed through Bray-Curtis similarity highlighted the climatic season’s rainy (May - October) and dry (November to April) associated changes in all the sampling sites over the period of one year study. Physico-chemicalvariables viz.electricconductivity, NO3 –, PO4 -3, SiO3 -2, calcium and hardness werethe key factors affecting the spatio- temporal distribution of plankton communities in this reservoir.The sampling sites in the study areas were selected at different zonation occurring in a reservoir such as lotic, intermediate, lentic in addition to two other confined zones falling off the mainstream. The presence of algal blooms in confined and intermediate zones of the reservoir during peak monsoon season (July) was attributed to the preï¿¾dominance ofdinoflagellate, Ceratium sp.and desmid, Closterium sp. respectively.ANOSIM analysis indicating significant dissimilarity in plankton abundance between lotic and lentic zone (29.7%) impliedthat climate driven water flow could be the reason for the variation. Keyword Plankton, spatio-temporal variation, oligotrophic reservoir.